Differential effects of chronotype on physical activity and cognitive performance in older adults - Hicks, Hilary; Meyer, Kayla; Watts, Amber (Frontiers in Epidemiology, 2023)
Chronotypes reflect individuals’ preferred activity and sleep patterns (e.g., “morning-types” vs. “evening-types”) and are associated with health and physical activity. Less is known about the relationship between chronotype and cognitive health in older adults. It is unclear whether chronotype’s influence is driven by sleep timing or disruption. This study explored the relationship between chronotype, physical activity, and cognitive performance in older adults with and without self-reported sleep disorders. Participants were 153 older adults (M = 70.35, SD = 5.89) who wore an Actigraph on the non-dominant wrist for seven days to measure total physical activity, peak physical activity, and chronotype (sleep interval midpoint). We categorized participants as morning-, evening-, and intermediate-chronotypes and assessed cognitive performance in domains of attention, executive function, and verbal memory. MANCOVAs showed patterns of activity across the 24-hour day differed between chronotypes such that morning-types were active earlier and evening-types active later, ps > .001. Total physical activity and average peak activity did not differ between chronotypes, (ps ≥ .117). Timing of peak activity followed expectations (morning-types peaked earliest (p = .019)). Evening-types exhibited significantly worse executive function and attention than intermediate-types, p = .008. When excluding participants with sleep disorders, evening-types engaged in significantly less total physical activity than other groups, but cognitive performance did not differ. We found no differences in total or peak physical activity between groups, which is inconsistent with findings from studies in younger samples. This suggests the role of chronotype on physical activity may change with age and points to the potential impact of methodological discrepancies. While evening-types exhibited worse executive function and attention performance, this finding disappeared when participants with sleep disorders were excluded. Sleep dysregulation rather than sleep timing may be driving this difference. Recent trends in physical activity research explore activity patterns across the 24-hour day and acknowledge codependence between different activity types. Our findings suggest chronotype and activity timing may be important as researchers advance this line of research in older adults.